2018
DOI: 10.1111/acem.13656
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Emergency Care Research Networks: A Research Agenda

Abstract: Background: Pediatric emergency care research networks have evolved substantially over the past two decades. Some networks are specialized in specific areas (e.g., sedation, simulation) while others study a variety of medical and traumatic conditions. Given the increased collaboration between pediatric emergency research networks, the logical next step is the development of a research priorities agenda to guide global research in emergency medical services for children (EMSC).Objectives: An international group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…Other topics, such as ‘implementation of knowledge’, ‘pathways of managing ED conditions’ and ‘in-house simulation’ reflect the need to efficiently implement knowledge into clinical ED practice. Dissemination and implementation of evidence-based guidelines for emergent conditions, customised to local practice is important,11 in particular considering the large number of children presenting to European EDs annually and the heterogeneous status of PEM in Europe. This will ensure provision of up-to-date optimal care, reduce variation in practice, improve patient outcome and experience of care as well as optimise resource utilisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other topics, such as ‘implementation of knowledge’, ‘pathways of managing ED conditions’ and ‘in-house simulation’ reflect the need to efficiently implement knowledge into clinical ED practice. Dissemination and implementation of evidence-based guidelines for emergent conditions, customised to local practice is important,11 in particular considering the large number of children presenting to European EDs annually and the heterogeneous status of PEM in Europe. This will ensure provision of up-to-date optimal care, reduce variation in practice, improve patient outcome and experience of care as well as optimise resource utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…We still need to promote inclusiveness of European countries' participation to PEM research to ensure a broad and diverse representation. Furthermore, we need to foster collaboration with patients and their families, for example, to include patient-centred and patient-reported outcomes in future study projects 7 11. This will ensure that the network’s research projects are relevant to both paediatric emergency care end-users and clinicians alike.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation research has been identified as a global research priority for emergency medicine . However, several reviews undertaken to determine the volume and quality of implementation research in emergency medicine have found very limited evidence in general, and in Australasia in particular .…”
Section: Implementation Of Evidence In the Edmentioning
confidence: 99%
“…Implementation research has been identified as a global research priority for emergency medicine. 22,23 However, several reviews undertaken to determine the volume and quality of implementation research in emergency medicine have found very limited evidence in general, and in Australasia in particular. 7,24 Authors have recommended more high-quality rigorous research that uses theory-based approaches to identify the key factors influencing practice variation to inform the design and evaluation of targeted implementation interventions.…”
Section: Implementation Of Evidence In the Edmentioning
confidence: 99%